Investigasi kemanusiaan : studi investigasi kemanusiaan terhadap peristiwa Koja, Tanjung Priok, 14 April 2010 - Palang Merah Indonesia (Jakarta, Indonesia : Madani Institute, 2010)
Legal and social perspectives on human rights violation during a clash in Koja, Tanjung Priok, Jakarta, April 14, 2010; result of an investigation of Indonesian Red Cross.
Keywords: Human rights -- Indonesia -- Jakarta